2003
DOI: 10.1002/elps.200305452
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis in anti‐cancer metallodrug research: Advances and future challenges

Abstract: An efficient and convenient separation method has been a long sought after goal for anti-cancer metallodrug developers. For many reasons, capillary electrophoresis (CE) has recently emerged as the method of choice for the separation of intact platinum metal complexes and their metabolites, assessment of drug stability, and studying the interaction of the administered and potential tumor-inhibiting metallocomplexes with biomolecules. Due to the application of gentle separation conditions and successful developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…CE has been used to determine chemical equilibria in proteinmetallodrug systems [49,50]. Compared with other separation-based assays such as highperformance liquid chromatography (HPLC), CE possesses distinctive advantages such as shorter analysis time, use of electrolyte compositions compatible with physiological incubation conditions, and no stationary phase involved in separation [51]. A similar approach as in the spectroscopic studies was followed with the HSA-to-site marker ratio kept constant and the KP1019 and KP1339 content was varied.…”
Section: Resultsmentioning
confidence: 99%
“…CE has been used to determine chemical equilibria in proteinmetallodrug systems [49,50]. Compared with other separation-based assays such as highperformance liquid chromatography (HPLC), CE possesses distinctive advantages such as shorter analysis time, use of electrolyte compositions compatible with physiological incubation conditions, and no stationary phase involved in separation [51]. A similar approach as in the spectroscopic studies was followed with the HSA-to-site marker ratio kept constant and the KP1019 and KP1339 content was varied.…”
Section: Resultsmentioning
confidence: 99%
“…5. Sequence analysis showed that both 3 and 4 preferentially attack at A, C, and G (and not T), as expected based on their different basicities [42].…”
mentioning
confidence: 83%
“…Capillary electrophoresis has often been applied to the analysis of platinum group complexes as well as their interaction with biomolecules in recent years (Hartinger et al, 2003;Timerbaev et al, 2006). DNA is considered the critical target for platinum complexes, and competitive studies including all four nucleobases confirmed guanine (and to a lesser extent adenine) as the preferred binding partner for the metal complexes-adduct formation takes place mainly via the N7 of the nucleobase (Martin, 1999).…”
Section: Downloaded Frommentioning
confidence: 99%